Respuesta :

Answer:

The correct answer is C.

Step-by-step explanation:

To find this, we need to note that in order to reverse the function of raising the b to the x power, we need to take the log base b of the function. Since the answer C is the only one containing that, it must be the correct answer,

The inverse of the given function is expressed as [tex]g^{-1}(y)=log_xb[/tex]

Given the exponential function [tex]g(x)=b^x[/tex]

Let y = f(x), to have [tex]y = b^x[/tex]

Replace y with x to have:

[tex]x=b^y[/tex]

Make y the subject of the formula by taking the log of both sides

[tex]logx=logb^y\\logx=ylogb[/tex]

Divide both sides by log b

[tex]y=\frac{logx}{log b} \\y = log_xb[/tex]

Hence the inverse of the given function is expressed as [tex]g^{-1}(y)=log_xb[/tex]

learn more here: https://brainly.com/question/11735394

ACCESS MORE